2017
DOI: 10.1039/c7bm00414a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of black phosphorus–Au nanocomposites for enhanced photothermal cancer therapy and surface-enhanced Raman scattering analysis

Abstract: Black phosphorus (BP), a new type of two-dimensional nanomaterial, has attracted crucial attention in recent years owing to its excellent properties and great potential in various chemical, physical, and biological fields. In this study, BP nanosheets loaded with Au nanoparticles (BP-Au NSs) are obtained by a one-step facile synthetic method. The Au nanostructures can not only enhance the photothermal efficiency of the nanocomposites, but also endow BP-Au NSs with the potential to act as effective surface-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…The integration of plasmonic metal nanomaterials with 2D nanomaterials is another approach for enhanced light absorption via the plasmonic near‐field effect, compared with its individual component. Guo and co‐workers synthesized BP‐Au nanosheets, and confirmed that BP‐Au nanosheets could improve photothermal conversion efficiency compared with BP nanosheets . In another report, core–shell Pd@Au nanoplates with high photothermal conversion efficiency were fabricated for PTT (Figure e,f) .…”
Section: D Nanomaterials For Pttmentioning
confidence: 84%
“…The integration of plasmonic metal nanomaterials with 2D nanomaterials is another approach for enhanced light absorption via the plasmonic near‐field effect, compared with its individual component. Guo and co‐workers synthesized BP‐Au nanosheets, and confirmed that BP‐Au nanosheets could improve photothermal conversion efficiency compared with BP nanosheets . In another report, core–shell Pd@Au nanoplates with high photothermal conversion efficiency were fabricated for PTT (Figure e,f) .…”
Section: D Nanomaterials For Pttmentioning
confidence: 84%
“…BP nanosheets are first modified with Au nanoparticles (BP–Au NSs) by a one‐step facile synthetic method that enhances the efficiency of PTT . Compared to bare BP nanosheets, the absorption capacity of BP–Au NSs is improved in the NIR region, resulting in an excellent photothermal effect.…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%
“…Surface‐Enhanced Raman Scattering Imaging : Surface‐enhanced Raman spectroscopy (SERS) offers the advantage of high sensitivity and is a powerful trace analysis technique for the detection of analytes at low concentration. Yang et al prepared BP nanosheets modified with Au nanoparticles (BP–Au NSs) for SERS bioanalysis (Figure D). The Au nanostructure equipped BP–Au NSs with the potential to be used as an effective SERS substrate for Raman biological detection.…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 193 prepared FLBP coated with Au nanoparticles for surface-enhanced Raman scattering (SERS) imaging. BP-Au NSs were fabricated with a facile re°ux method, and mPEG-SH was added to improve the dispersion and stability in water.…”
Section: Tumor Imagingmentioning
confidence: 99%